Teknik Relaksasi Otogenik terhadap Tingkat Stres pada Lansia - I Dewa Made Ruspawan; I Gede Widjanegara (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2015)
The purpose of this study was to determine the effect of autogenic relaxation on the level of stress on the elderly in the Region Health Center of northern Kuta Badung. This study is a quasi experiment with pretest and posttest with control group. Samples were taken from two different places, namely at Canggu Banjar Permai village as a treatment group and Tegalgundul village as a control group. The sampling technique used purposive sampling by the number of samples in the treatment group as many as 18 people, while in the control group of 16 people. The technique of collecting data using questionnaires Depression, Anxiety, and Stress Scales (DASS) with ratio scale. From the statistical test independent sample T-test showed p = 0.001 (p 0.05), which meaning that there are influence of autogenic relaxation on level of stress.